2020
DOI: 10.1371/journal.pone.0233947
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen reduction of SARS-CoV-2 virus in plasma and whole blood using riboflavin and UV light

Abstract: BackgroundSevere Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has recently been identified as the causative agent for Coronavirus Disease 2019 . The ability of this agent to be transmitted by blood transfusion has not been documented, although viral RNA has been detected in serum. Exposure to treatment with riboflavin and ultraviolet light (R + UV) reduces blood-borne pathogens while maintaining blood product quality. Here, we report on the efficacy of R + UV in reducing SARS-CoV-2 infectivity when te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 21 publications
(25 reference statements)
5
47
0
1
Order By: Relevance
“…The effectiveness of UV on SARS-CoV-2 was recently reported: Heilingloh et al [97] demonstrated that UV irradiation represents a suitable disinfection method for SARS-CoV-2, since a total inactivation of a viral stock of SARS-CoV-2 at a concentration of 5 × 10 6 TCID50/mL was achieved after 9 min of combined UVA and UVC exposure. Moreover, we assessed that exposure to riboflavin and ultraviolet light (R + UV) reduces the infectious titre of SARS-CoV-2 below the limit of detection in plasma products [98]. These studies are in line with a previous research that demonstrated inactivation by UV light of closely-related viruses such as SARS-CoV, MERS, and other respiratory viruses [99].…”
Section: Potential Approaches To Reduce the Risk Of Sars-cov-2 Contamsupporting
confidence: 74%
“…The effectiveness of UV on SARS-CoV-2 was recently reported: Heilingloh et al [97] demonstrated that UV irradiation represents a suitable disinfection method for SARS-CoV-2, since a total inactivation of a viral stock of SARS-CoV-2 at a concentration of 5 × 10 6 TCID50/mL was achieved after 9 min of combined UVA and UVC exposure. Moreover, we assessed that exposure to riboflavin and ultraviolet light (R + UV) reduces the infectious titre of SARS-CoV-2 below the limit of detection in plasma products [98]. These studies are in line with a previous research that demonstrated inactivation by UV light of closely-related viruses such as SARS-CoV, MERS, and other respiratory viruses [99].…”
Section: Potential Approaches To Reduce the Risk Of Sars-cov-2 Contamsupporting
confidence: 74%
“…Table 1 also includes the results of one study that investigated the impact of deep-UV light at 280 nm (i.e., the boundary between UV-B and UV-C) on SARS-CoV-2 (Inagaki et al, 2020). In addition, three studies were found that used a combination of UV-A and UV-B light (270-360 nm), together with the photosensitiser, riboflavin, to disinfect SARS-CoV-2 Ragan et al, 2020) and MERS-CoV (Keil, Bowen & Marschner, 2020) in blood products (Table 2). Although these studies did not utilize UV-C light, it was nevertheless decided to report the results of these studies here so that direct comparisons could be made between SARS-CoV-2 and MERS-CoV.…”
Section: Analysis Of the Published Literaturementioning
confidence: 99%
“…Since the emergence of COVID-19 in January 2020 there has been considerable interest in the use of ultraviolet (UV) light to disinfect blood plasma (Eickmann et al, 2020;Ragan et al, 2020), equipment (Card et al, 2020;Derraik et al, 2020;Hamzavi et al, 2020;Heimbuch & Harnish, 2019) and air (Morawska et al, 2020), in the hope that this might reduce transmission of the disease. In particular, upper-room ultraviolet germicidal irradiation (UVGI), a technology that disinfects room air, has…”
Section: Introductionmentioning
confidence: 99%
“…Blood product screening for viruses may have a high false-negative rate which questions its usefulness, similar to what happened during the SARS outbreak [ 8 , 9 ]. Nevertheless, pathogen reduction (PR) on blood products using riboflavin and UV (UV) light has been shown to be effective in reducing SARS-CoV-2 infectivity [ 10 ].…”
Section: Blood Product Safetymentioning
confidence: 99%
“…The outer layer of biohazard plastic bag and container should be disinfected prior to transportation. In some centres, UV irradiation is used for disinfection prior to laboratory processing [ 10 , 15 ].…”
Section: Transfusion Testing and Blood Supply For Patients With Covid-19mentioning
confidence: 99%